A Six-Minute Walk Test: Oxygen Uptake and Distance Predicted - Vásquez-Gómez, Jaime (2022)
Background: Maximum oxygen consumption is an indicator of cardiorespiratory fitness. Aim: The purpose was, first, to relate and compare the V̇O2max as the dependent variable with the estimated distance in the six-minute walk test (SMWT) as the independent variable in university students and, secondly, to relate the distance (dependent) with demographic and anthropometric variables (independents). Methodology: A correlational, descriptive, and quantitative study with a non-experimental design was conducted on 110 university students. In the study, basic anthropometry and vital signs were measured. A direct method of V̇O2max (Bruce test) on a treadmill was applied. Then, the distance covered in the SMWT was evaluated with two equations available in the scientific literature. Differences between men and women were measured in the tests, the correlation between the distances estimated with V̇O2max and anthropometric variables, and repeated ANOVA measurement tests between V̇O2max and estimated distance were analyzed with the SPSS v.22 program (p<0.05). Results: Significant correlations were found between V̇O2max and estimated distances (p<0.05) in the total sample, men and women, and in some cases, the distance correlated with gender, age, weight, height, and BMI (p<0.05). However, there were differences between V̇O2max and distances estimated in the SMWT (p<0.001). Conclusions: The V̇O2max measurement method is different from the distance prediction equations, although they have a significant relationship.